Preparation method of SnSe-SnSe2 composite crystal

By preparing SnSe-SnSe2 composite crystal under low sealing temperature and low energy consumption conditions, combined with melt method and chemical gas phase transport method, the problem of inconspicuous elemental selenium impurities and layered structure is solved, and the preparation effect of high-quality and low energy consumption is achieved.

CN119663448APending Publication Date: 2025-03-21QIQIHAR UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411876766.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has problems such as elemental selenium impurities, lack of layered structure, and high temperature and high energy consumption when preparing SnSe-SnSe2 composite crystals, which is difficult to meet the needs of manufacturing high-performance devices.

Method used

Using a method of low sealing temperature and low energy consumption, a modified muffle furnace and resistive wire sealing equipment was heat sealed under argon protection, and combined with melt method and chemical gas phase transport method, SnSe-SnSe2 composite crystal was prepared.

Benefits of technology

Efficient removal of elemental selenium impurities, enhance the formation of layered structures, reduce production costs and energy consumption, and significantly improve the crystallinity and orientation of SnSe-SnSe2 composite crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663448A_ABST
    Figure CN119663448A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of condensed state physics, and discloses a preparation method of a SnSe-SnSe2 composite crystal, which comprises the following steps: S1, drying a cleaned high-boron glass tube, and naturally cooling the dried high-boron glass tube to room temperature; s2, tin, selenium and iodine are jointly placed in a high-boron glass tube according to the proportion, and the high-boron glass tube is subjected to heat sealing under argon protection; and S3, placing the high-boron glass tube in an improved muffle furnace, firstly raising the temperature in the furnace to 690-750 DEG C at a heating rate of 1-10 DEG C / min, maintaining the temperature for 12-60 hours, then reducing the temperature in the furnace to 250 DEG C at a cooling rate of 0.05-0.3 DEG C / min, and finally reducing the temperature in the furnace to room temperature through natural cooling. In conclusion, the preparation method of the SnSe-SnSe2 composite crystal provided by the invention has remarkable advantages in the aspects of lamellar structure, no impurity, energy efficiency, environmental protection and the like, has wide application potential, and particularly has important application value in the fields of electronics, photoelectricity and thermoelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of condensed matter physics, and specifically relates to a SnSe-SnSe 2 A method for preparing composite crystals. Background Art

[0002] SnSe and SnSe 2 As layered late transition metal chalcogenides, they exhibit excellent semiconductor properties. SnSe has significant anisotropic conductivity, extremely low thermal conductivity and excellent power factor; while SnSe 2 They show excellent carrier mobility, photocurrent generation capability and high electron affinity. Both materials have wide application value in electronics, optoelectronics and thermoelectrics. They also have good chemical stability, abundant raw material sources and low production costs, as well as non-toxic and pollution-free environmental advantages, making them ideal choices for related research and application fields.

[0003] In recent years, SnSe-SnSe 2 Composite systems have received more and more attention, and research has focused on developing new composite materials by combining the excellent properties of both through reasonable design. 2 Composite films and heterojunctions can effectively adjust the band gap of materials, optimize light response performance, and combine the advantages of both to promote the development of new functional materials. However, current research focuses on SnSe-SnSe 2 Preparation of composite thin films and heterojunctions, and about SnSe-SnSe 2 Research on composite crystals is still relatively limited.

[0004] At present, the melt method is the preparation of SnSe-SnSe 2 The main method of composite crystals, but this method has the following outstanding problems:

[0005] 1. Impurity problem of elemental selenium: SnSe-SnSe prepared by melt process 2 Elemental selenium impurities are often present in composite crystals, which leads to reduced crystallinity of the system, thus affecting the stability and life of the device.

[0006] 2. The layered structure is not obvious: Due to the poor orientation of the crystals during the melt preparation process, the layered structure is not obvious, which makes it difficult to mechanically peel the crystals, thereby affecting the acquisition of high-quality thin film materials and limiting their application in high-performance devices.

[0007] 3. High temperature, high energy consumption and operational hazards: The melt method usually needs to be carried out at high temperature, such as using a flame-encapsulated quartz glass tube to heat to above 1200°C, which not only consumes a lot of energy, but also poses operational safety hazards, especially when using flammable gases, which increases the complexity of the operation and production costs.

[0008] Therefore, the main challenge facing the existing technology is how to prepare high-quality SnSe-SnSe safely and without impurities under low temperature and low energy consumption conditions. 2 Composite crystals and improve the significance of their layered structure, crystal orientation and crystallinity to meet the needs of manufacturing high-performance devices. Summary of the invention

[0009] In view of this, in order to solve the problems raised in the above background technology, the object of the present invention is to provide a SnSe-SnSe 2 A method for preparing a composite crystal. The method can effectively remove elemental selenium impurities, enhance the formation of a layered structure, and reduce production costs while ensuring operational safety.

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] A SnSe-SnSe 2 A method for preparing a composite crystal, comprising:

[0012] S1. Dry the cleaned boron glass tube and allow the dried boron glass tube to cool naturally to room temperature;

[0013] S2. Place tin, selenium and iodine together in a high-boron glass tube in proportion, and heat-seal the high-boron glass tube under argon protection;

[0014] S3. Place the high-boron glass tube in a modified muffle furnace, first raise the temperature in the furnace to 690-750°C at a heating rate of 1-10°C / min and maintain it for 12-60h, then lower the temperature in the furnace to 250°C at a cooling rate of 0.05-0.3°C / min, and finally lower the temperature in the furnace to room temperature through natural cooling.

[0015] Preferably, the cleaning step of the high-boron glass tube comprises:

[0016] S11. Use detergent soap to preliminarily clean the high boron glass tube, and then rinse it with distilled water to ensure that there are no small water droplets attached to the surface of the high boron glass tube;

[0017] S12. The high boron glass tube was immersed in a 0.03% dilute hydrochloric acid solution, ultrasonically cleaned for 5 minutes, and then removed and washed with distilled water;

[0018] S13. Soak the borosilicate glass tube in anhydrous ethanol, clean it ultrasonically for 5 minutes, take it out and clean it again with distilled water.

[0019] Preferably, the drying step of the high-boron glass tube comprises: placing the cleaned high-boron glass tube into a constant temperature drying oven and drying at 140° C. for 30 minutes.

[0020] Preferably, the tin is tin particles with a purity of ≥99.99%, the selenium is selenium particles with a purity of ≥99.99%, and the chemical ratio of the tin particles to the selenium particles is 1:1.1 to 1:1.9.

[0021] Preferably, the iodine accounts for 0.01% to 0.125% of the total mass of the tin particles and the selenium particles.

[0022] Preferably, the heat sealing step of the high-boron glass tube comprises:

[0023] S21. The boron glass tube containing tin, selenium and iodine is evacuated, and after the vacuum reaches ≤0.005Pa, high-purity argon gas with a purity of ≥99.99% is introduced, and the pressure in the boron glass tube is adjusted to 2000Pa;

[0024] S22. Place the high-boron glass tube under argon protection in a resistance wire sealing device for heat sealing.

[0025] Preferably, the heat sealing temperature is 830-900°C.

[0026] More preferably, the heat sealing temperature is 870°C.

[0027] Preferably, the muffle furnace is improved in that a hole with a diameter of 10 cm is opened at the furnace door, and the hole is blocked with a furnace plug to form a natural temperature gradient of 80° C. in the furnace.

[0028] Preferably, the high-boron glass tube is placed flat in the improved muffle furnace.

[0029] Preferably, both ends of the high-boron glass tube are respectively close to the furnace door and the thermocouple in the furnace, with the end close to the thermocouple being the reaction end of the high-boron glass tube, and the tin, selenium and iodine are all concentrated at the reaction end of the high-boron glass tube.

[0030] Further preferably, the high-boron glass tube is placed in a modified muffle furnace, the temperature in the furnace is first raised to 720°C at a heating rate of 5°C / min and then maintained for 36 hours, then the temperature in the furnace is lowered to 250°C at a cooling rate of 0.2°C / min, and finally the temperature in the furnace is lowered to room temperature by natural cooling.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) Reducing experimental temperature and risk: The present invention adopts a low-melting-point high-boron glass tube to replace the traditional pure quartz glass tube, and uses a resistance wire sealing device to complete the packaging at a temperature below 900°C, avoiding the high-temperature operation required in the traditional flame packaging process.

[0033] (2) Optimizing equipment and energy efficiency: The present invention adopts an improved muffle furnace and ingeniously forms a temperature gradient of 80°C from the furnace chamber to the furnace door. By combining low-concentration iodine as the gas phase transport medium, the melt method and the chemical vapor transport method are effectively combined. This design not only avoids SnSe-SnSe 2 The formation of common elemental selenium impurities in the composite crystal synthesis process can also obtain high-quality SnSe 2 Single wafer layers are produced as a by-product. Significantly reduces energy consumption compared to conventional two-zone furnaces.

[0034] (3) Significant anisotropy and layered structure: SnSe-SnSe synthesized by the method of the present invention 2 The composite crystals exhibited obvious anisotropy and layered structure. The powder and layer X-ray diffraction (XRD) results showed that SnSe 2 The diffraction peak intensities of (001), (002), (003), and (004) of the SnSe phase are significantly enhanced compared to the corresponding peaks in the standard card, and the diffraction peak intensity of the SnSe phase (400) is also increased. The intensity of the corresponding diffraction peak is significantly higher than the peak intensity of conventional XRD scanning, especially when the scanning rate is 5° / min. 2 The (001) crystal plane diffraction peak intensity of the phase reached 692766 count units, which is much higher than the conventional peak intensity, indicating that the composite crystal has a strong crystal orientation. 2 The (001) crystal plane diffraction peak of SnSe is the strongest among all the diffraction peaks. 2 The (011) crystal plane peak of SnSe is usually the strongest; the (400) crystal plane diffraction peak of SnSe is the strongest among all its diffraction peaks, and the (111) crystal plane peak of SnSe in the standard card is usually the strongest; these diffraction characteristics indicate that SnSe 2 and SnSe grow perpendicular to their respective van der Waals layers along the (001) and (100) directions, further verifying the SnSe-SnSe 2 The composite crystals have superiority in layered structure and show that SnSe 2 A stable van der Waals layer stacking is formed between SnSe, maintaining a unique layered arrangement structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 SnSe-SnSe 2Comparison results of XRD patterns of composite crystal powder and standard cards;

[0036] Figure 2 SnSe-SnSe 2 X-ray photoelectron spectroscopy (XPS) of the Sn 3d electronic state in the composite crystal;

[0037] Figure 3 SnSe-SnSe 2 Composite Crystal SnSe 1.54 Lamellar XRD pattern;

[0038] Figure 4 SnSe-SnSe 2 Surface morphology and cross-sectional morphology of the composite crystal;

[0039] Figure 5 SnSe 2 XRD diffraction pattern and surface morphology of single crystal. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Example 1

[0042] A SnSe-SnSe 2 A method for preparing a composite crystal, comprising:

[0043] S1. Pretreatment of high boron glass tube

[0044] S11. Use washing soap to preliminarily clean the high boron glass tube, and then rinse with distilled water to ensure that there are no small water droplets or water droplets attached to the surface of the high boron glass tube (in this step, the cleaned high boron glass tube can be placed in a room temperature environment to dry naturally, or preferably use a laboratory test tube hot air dryer);

[0045] S12. The high boron glass tube was immersed in a 0.03% dilute hydrochloric acid solution, ultrasonically cleaned for 5 minutes, and then removed and washed with distilled water;

[0046] S13. Soak the high-boron glass tube in anhydrous ethanol, ultrasonically clean it for 5 minutes, and then take it out and clean it again with distilled water;

[0047] S14. Place the cleaned high-boron glass tube into a constant temperature drying oven, dry at 140°C for 30 minutes, and then cool naturally to room temperature.

[0048] S2. Raw material processing

[0049] S21. Weigh high-purity tin particles (purity ≥ 99.99%) and selenium particles (purity ≥ 99.99%) according to a chemical ratio of 1:1.5, weigh 8 g of the total mass of the tin particles and selenium particles, and weigh 5 mg of iodine particles, and place all the weighed raw materials in a high-boron glass tube;

[0050] S22. The boron glass tube containing tin, selenium and iodine is evacuated, and after the vacuum reaches ≤0.005Pa, high-purity argon gas with a purity of ≥99.99% is introduced, and the pressure in the boron glass tube is adjusted to 2000Pa (this step is repeated at least twice to fully remove gas impurities in the boron glass tube);

[0051] S23. Place the high boron glass tube under argon protection in a resistance wire sealing device and heat seal the high boron glass tube at 870°C;

[0052] S3. High temperature reaction

[0053] S31. Improved (small) muffle furnace: A hole with a diameter of 10 cm was opened at the furnace door, and the hole was blocked with a furnace plug to form a natural temperature gradient of 80°C in the furnace;

[0054] S32. Place a high boron glass tube in a flat manner in the improved muffle furnace, with the two ends of the high boron glass tube close to the furnace door and the thermocouple in the furnace respectively, with the end close to the thermocouple as the reaction end of the high boron glass tube, and the tin, selenium and iodine are all concentrated at the reaction end of the high boron glass tube;

[0055] S3. Raise the temperature in the furnace to 720°C at a heating rate of 1 to 10°C / min and maintain for 36 hours;

[0056] S4. The temperature in the furnace is lowered to 250°C at a cooling rate of 0.2°C / min, and then the temperature in the furnace is lowered to room temperature by natural cooling.

[0057] Example 2

[0058] A SnSe-SnSe 2 A method for preparing a composite crystal, comprising:

[0059] S1. Pretreatment of high-boron glass tube (same as in Example 1);

[0060] S2. Raw material processing (weighing high-purity tin particles and selenium particles according to a chemical ratio of 1:1.6, and the remaining steps are the same as in Example 1);

[0061] S3. High temperature reaction (same as Example 1).

[0062] Example 3

[0063] A SnSe-SnSe 2 A method for preparing a composite crystal, comprising:

[0064] S1. Pretreatment of high-boron glass tube (same as in Example 1);

[0065] S2. Raw material processing (weighing high-purity tin particles and selenium particles according to a chemical ratio of 1:1.7, and the remaining steps are the same as in Example 1);

[0066] S3. High temperature reaction (same as Example 1).

[0067] Example 4

[0068] A SnSe-SnSe 2 A method for preparing a composite crystal, comprising:

[0069] S1. Pretreatment of high-boron glass tube (same as in Example 1);

[0070] S2. Raw material processing (weighing high-purity tin particles and selenium particles according to a chemical ratio of 1:1.8, and the remaining steps are the same as in Example 1);

[0071] S3. High temperature reaction (same as Example 1).

[0072] After the reaction of the above-mentioned examples 1 to 4, SnSe-SnSe is formed at the reaction end of the high boron glass tube. 2 Composite crystal, the cold end near the furnace door obtains the by-product SnSe 2 Single crystal layer.

[0073] Energy dispersive X-ray spectroscopy (EDX) analysis revealed that the SnSe-SnSe prepared at different initial feed ratios (1:1.5, 1:1.6, 1:1.7, and 1:1.8) 2 Atomic composition of composite crystals:

[0074] like Figure 1 As shown in the figure, SnSe 1.28 SnSe 1.54 SnSe 1.72 and SnSe 1.81 Corresponding to these different feed ratios, the comparison with the standard card shows that the composite crystal consists of two phases:

[0075] —SnSe 2 phase (space group P 3M1) and SnSe phase (space group PNMA), and no selenium or other impurity phases were observed. SnSe 2The phase shows obvious diffraction characteristics at characteristic diffraction peaks such as (001), (003), (110) and (004), especially the (001) peak, indicating that SnSe 2 The SnSe phase preferentially grows along the (001) direction; the SnSe phase has characteristic peaks at the diffraction peaks of (201), (111), (400), (311) and (511), among which the (400) peak is particularly prominent, indicating that the SnSe grows along the (100) direction. As the selenium content decreases, the XRD diffraction intensity of the SnSe phase gradually weakens, indicating that the SnSe 2 The proportion of SnSe gradually increases and finally becomes the dominant phase. 2 The (001) diffraction peak of the phase shifts to higher angles as its proportion increases.

[0076] like Figure 2 As shown, through Sn 2+ and Sn 4+ The analysis of the spectrum peaks further verified that SnSe 2 Coexistence of SnSe and SnS phases in composite crystals.

[0077] like Figure 3 As shown, SnSe 2 The (001) diffraction peaks and the SnSe (400) diffraction peaks are relatively strong, indicating that SnSe 2 and SnSe grow perpendicular to their respective van der Waals layers along the (001) and (100) directions, respectively. This result further verifies the SnSe-SnSe 2 The layered structure of the composite crystal shows that SnSe 2 A stable van der Waals layer stacking structure is formed between SnSe, thus maintaining a unique layered arrangement.

[0078] like Figure 4 As shown, the figure shows different samples (SnSe 1.28 SnSe 1.54 and SnSe 1.81 ) surface characteristics, where SnSe 1.28 The surface of SnSe is loose and irregular, showing a layered structure; 1.54 To SnSe 1.81 The surface texture of SnSe is smoother and the layered structure is clearer. 1.72 The cross-sectional morphology shows an obvious layered structural framework, further proving that this series of composite crystals have good mechanical exfoliation properties.

[0079] like Figure 5 As shown, SnSe as a by-product 2 The single crystals exhibited a clear layered structure without impurities and obvious defects.

[0080] In summary, SnSe-SnSe was successfully prepared by a low sealing temperature (870°C), low energy consumption, safe and simple melt-chemical vapor transport hybrid method. 2 Composite crystals. These crystals exhibit clear layered structures, no selenium impurities, and high-quality characteristics, which fully verify the effectiveness and superiority of the method of the present invention. They have significant advantages in terms of layered structure, no impurities, energy efficiency, and environmental protection, and have broad application potential, especially in the fields of electronics, optoelectronics, and thermoelectric devices.

[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a SnSe-SnSe2 composite crystal, characterized in that: include: S1. Dry the cleaned boron glass tube and allow the dried boron glass tube to cool naturally to room temperature; S2. Place tin, selenium and iodine together in a high-boron glass tube in proportion, and heat-seal the high-boron glass tube under argon protection; S3. Place the high-boron glass tube in a modified muffle furnace, first raise the temperature in the furnace to 690-750°C at a heating rate of 1-10°C / min and maintain it for 12-60h, then lower the temperature in the furnace to 250°C at a cooling rate of 0.05-0.3°C / min, and finally lower the temperature in the furnace to room temperature through natural cooling.

2. The method for preparing a SnSe-SnSe2 composite crystal according to claim 1, characterized in that: The cleaning step of the high boron glass tube comprises: S11. Use detergent soap to preliminarily clean the high boron glass tube, and then rinse it with distilled water to ensure that there are no small water droplets attached to the surface of the high boron glass tube; S12. The high boron glass tube was immersed in a 0.03% dilute hydrochloric acid solution, ultrasonically cleaned for 5 minutes, and then removed and washed with distilled water; S13. Soak the borosilicate glass tube in anhydrous ethanol, clean it ultrasonically for 5 minutes, take it out and clean it again with distilled water.

3. The method for preparing a SnSe-SnSe2 composite crystal according to claim 1, characterized in that: The drying process of the high-boron glass tube comprises: The cleaned high boron glass tube was placed in a constant temperature drying oven and dried at 140°C for 30 minutes.

4. The method for preparing a SnSe-SnSe2 composite crystal according to claim 1, characterized in that: The tin is tin particles with a purity of ≥99.99%, and the selenium is selenium particles with a purity of ≥99.99%, and the chemical ratio of the tin particles to the selenium particles is 1:1.1 to 1:1.

9.

5. The method for preparing a SnSe-SnSe2 composite crystal according to claim 4, characterized in that: The iodine accounts for 0.01% to 0.125% of the total mass of the tin particles and the selenium particles.

6. The method for preparing a SnSe-SnSe2 composite crystal according to claim 1, characterized in that: The heat sealing step of the high boron glass tube comprises: S21. The boron glass tube containing tin, selenium and iodine is evacuated, and after the vacuum reaches ≤0.005Pa, high-purity argon gas with a purity of ≥99.99% is introduced, and the pressure in the boron glass tube is adjusted to 2000Pa; S22. Place the high-boron glass tube under argon protection in a resistance wire sealing device for heat sealing.

7. The method for preparing a SnSe-SnSe2 composite crystal according to claim 6, characterized in that: The heat sealing temperature is 830-900°C.

8. The method for preparing a SnSe-SnSe2 composite crystal according to claim 1, characterized in that: The muffle furnace is improved in that a hole with a diameter of 10 cm is opened at the furnace door, and the hole is blocked with a furnace plug to form a natural temperature gradient of 80° C. in the furnace.

9. The method for preparing a SnSe-SnSe2 composite crystal according to claim 8, characterized in that: The high boron glass tube is placed flat in the improved muffle furnace.

10. The method for preparing a SnSe-SnSe2 composite crystal according to claim 9, characterized in that: The two ends of the high boron glass tube are respectively close to the furnace door and the thermocouple in the furnace, and the end close to the thermocouple is the reaction end of the high boron glass tube, and the tin, selenium and iodine are all concentrated at the reaction end of the high boron glass tube.